IMPLIKASI KEGIATAN PROGRAM DOSEN KE SEKOLAH (PDS) DI PERKULIAHAN PENDIDIKAN EKONOMI FKIP UNIVERSITAS SRIWIJAYA - Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
Learning activities carried out in educational research statistics courses in the FKIP Sriwijaya University economic education study program are an extension of the lecturer assignment program to schools (PDS) in 2018/2019. The learning model used in educationalresearch statistics courses is in accordance with the 2013 curriculum guidelines, namely the discovery learning, inquiry, Problem Based Learning and Project Based Learning methods. The learning models are applied for 8 times face to face with details of 2 times face to face applying the learning model of discovery learning; 2 second face-to-face approaches to inquiry learning; 2 times the third face to face applying the learning model of problem based learning; 2 times face to face applying discovery learning learning model; 2 times the fourth face to face applying the project based learning model. The PDS program in higher education has a positive impact on prospective teacher students to be able to understand more deeply about the learning situation that occurs in schools, ranging from the need for continuous motivation to students from the beginning of learning to closing learning in the form of giving reinforcement.